THE HISTORICAL VALUE OF THE KETUPAT WAR TRADITION IN AIR LINTANG VILLAGE TO GROW CULTURAL IDENTITY IN SMA NEGERI 1 TEMPILANG - Ela, Ela; Sukardi, Sukardi; Zamhari, Ahmad; Suriadi, Aan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
The historical value of the Ketupat War is a cultural heritage from the past in the people of Air Lintang Tempilang Village, West Bangka. Formulation of the problem for students who do not know the history and values contained in the ketupat war tradition; this ketupat war tradition fosters student cultural identity to find out the historical values contained in the Ketupat war tradition. This research method uses a qualitative descriptive method with data collection techniques using field data such as documentation and observation interviews. Data analysis techniques by presenting questionnaires and drawing conclusions. The results of this study show that there are historical values contained in the Ketupat War Tradition that foster the cultural identity of students at SMA Negeri 1 Tempilang.